Genome Mining and Synthetic Biology in Marine Natural Products Discovery - Costantini, Maria; Costantini, Maria (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In recent years, marine genomics has become a growning rapidly field, helped by the large amount of information that is becoming available to the international scientific community. Taking into account the current excitement in the field of marine biotechnology, this Special Issue entitled (3z(BGenome Mining and Synthetic Biology in Marine Natural Product Discovery(3y (Baims to to assess the impact of these molecular approaches on the discovery of bioactive compounds from marine organisms. The term (3z(Bgenome mining(3y (Bis used to identify all bioinformatic investigations aimed at detecting the biosynthetic pathways of bioactive natural products and their possible functional and chemical interactions. Several studies are now reporting on marine organisms. Oceans cover nearly 70% of the Earth$1 (Bs surface and host a huge ecological, chemical, and biological diversity. The natural conditions of the sea favor, in marine organisms, the production of a large variety of novel molecules with great pharmaceutical potential. Marine organisms are unique in their structural and functional features compared to terrestrial ones. Innovation in this field is very rapid, as revealed by the funding of several Seventh Framework Programme (FP7) and Horizon 2020 projects under the topic (3z(BBlue Growth(3y(B, with the urgent goal of discovering new drugs.s
English
Keywords: Technology: general issues; genome mining; global regulator; LaeA; overexpression; Penicillium dipodomyis; sorbicillinoids; ulvan-derived oligosaccharides; ulvan lyase; heterologous expression; polysaccharide lyase family 25; whole-genome sequencing; docosahexaenoic acid (DHA); polyunsaturated fatty acid; fatty acid synthesis pathway; polyketide synthase pathway; bacteria; fungi; natural products; synthetic biology; microalgae; monogalactosyldiacylglycerol synthase; UDP-sulfoquinovose synthase; sulfoquinovosyltransferase; monogalactosyldiacylglycerols; sulfoquinovosyldiacylglycerols; transcriptome analysis; n/a